The civil legal nature of credit relations in Ukraine - Hnat, Nadiia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
Credit relations arise on the basis of a credit agreement, which is a civil legal document, in writing, according to which one party (the lender) agrees to lend money (credit) to the other party - the borrower, and the borrower in turn agrees to repay granted him credit and pay interest within the period specified in the contract The lender, as a subjective element of the credit relationship, is the party that provides the loan to the borrower for the term specified in the contract. The lender may be a bank or other banking institution operating under a license. The benefit of the lender is to earn income in the form of credit interest. The borrower is a subject of credit relations, who receives a loan for a fixed term, undertakes to repay it, as well as to pay interest for the use of monetary assets. The borrower can be both an individual and a legal entity. The parties to the credit agreement acquire their status voluntarily after the conclusion of such agreement. For breach of obligations under the credit agreement, the parties bear civil liability, which is expressed in damages and penalties. The article studies the concept of credit agreement from the standpoint of civil law. The theoretical and legal characteristics of credit relations in Ukraine are given, their main features are highlighted. In the course of the research, a practical comparative analysis of loan agreements and loans was made, their common and distinctive features were distinguished. The responsibility of each party for breach of credit obligations has been determined.